The right to freedom of movement: human or political? - Borja Niño Arnaiz, (Las Torres de Lucca. International Journal of Political Philosophy, 2026)
There are two main approaches to freedom of movement: one is the freedom-centered view, which sees freedom of movement as an inherent aspect of human freedom; the other is the state-centered view, which sees freedom of movement as an eminently political right. In this article I develop a hybrid account that combines both approaches. On the one hand, I argue that freedom of movement is a human freedom right whose main purpose is the protection of autonomy. On the other hand, I argue that freedom of movement is a political right properly held against the state. Against the freedom-centered view, I conclude that there is no human right to international freedom of movement. Against the state-centered view, I contend that everyone within the state is entitled to freedom of movement irrespective of their citizenship.